Korelasi Kesiapan Belajar Siswa dan Pengelolaan Laboratorium Komputer terhadap Prestasi Belajar Siswa Pada Mata Pelajaran TIK di SMA Negeri Se-Kota Praya Tahun Ajaran 2012/2013 - Iman, Iman; Seri Wahyuni, Dessy; Mahendra Darmawiguna, I Gede (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aimed to determine (1) description of the correlation between students' learning readiness on student achievement in ICT subjects in high schools as the city of Praya, (2) a description of the correlation between the management of computer labs on student achievement in ICT subjects in SMA as the city of Praya, and (3) a description of the correlation between student readiness and management of computer labs bersam equally on student achievement in ICT subjects in high schools as the city of Praya. The population was students programs IPA XI and XII classes in SMA Se-Kota Praya, amounting to 797 students while the number of samples used in this study were as many as 266 people. Data collection methods used were interviews and questionnaires. The data analysis technique used is the parametric statistical analysis with the prerequisite test normality, homogeneity, linearity, and significance. The results showed that (1) there is a significant positive correlation between students' learning readiness on student achievement in ICT subjects in high schools as the city of Praya, (2) there is a significant positive correlation between the managing computer labs for student achievement students in ICT subjects in high schools as the city of Praya, and (3) there is a significant positive correlation between student readiness and laboratory management computers together on student achievement in ICT subjects in SMA Se-Kota Praya.